2012
DOI: 10.1074/jbc.m112.344622
|View full text |Cite
|
Sign up to set email alerts
|

HAMP Domain Signal Relay Mechanism in a Sensory Rhodopsin-Transducer Complex

Abstract: Background: HAMP domains are four-helix bundles that transmit signals from receptor to output domains in signaling proteins/complexes. Results: Opposite stimulus-induced helix motions with opposite signal output are resolved for two tandem HAMP domains on a phototaxis transducer. Conclusion: A molecular mechanism for HAMP domain switching and signal transmission is proposed. Significance: The HAMP switching and relay mechanism is important to many signal transduction proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 37 publications
7
30
0
Order By: Relevance
“…This supports the idea that other HAMP domains may oscillate between HAMP1 and HAMP2 to change output states. Furthermore, the data indicated that signal transduction through tandem HAMP domains involves alternating switching in conformer states [28], as proposed from the Aer2 structures [7].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This supports the idea that other HAMP domains may oscillate between HAMP1 and HAMP2 to change output states. Furthermore, the data indicated that signal transduction through tandem HAMP domains involves alternating switching in conformer states [28], as proposed from the Aer2 structures [7].…”
Section: Discussionmentioning
confidence: 57%
“…Recently Wang et al [28] reported ESR and labeling measurements using a more stable nanodisc-solubilized NpHtrII HAMP1-2 construct. Contrary to the previous report [27], they did not observe the unstable, dynamic HAMP state that had been seen in different salt concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Later, a similar structure was observed in a crystallographic structure of three consecutive HAMP domains from the Aer2 protein of Pseudomonas aeruginosa [6]. The arrangement was also verified by biochemical and biophysical methods for a number of other proteins – chemoreceptors Tar and Tsr [7][10], aerotaxis protein Aer [11], [12], phototaxis signal transducer HtrII [13][16] and sensory histidine kinases EnvZ and NarX [17], [18].…”
Section: Introductionsupporting
confidence: 58%
“…Nonsolubilized material was removed by ultracentrifugation, and protein was purified from the supernatant using a nickel-nitrilotriacetic acid column (Qiagen). The protein samples were concentrated in 100 mM NaCl, 0.02% dodecyl maltoside, 20 mM HEPES (pH 7.4) and used for measurements either directly or after reconstitution in nanodiscs with 1,2-dimyristoyl-sn-glycero-3-phosphocholine lipid from Avanti Polar Lipids (Alabaster, AL), as described for haloarchaeal sensory rhodopsin II in (34).…”
Section: Whole Cell Patch Clamp Measurements In Hek293 Cells-mentioning
confidence: 99%